Put it in the bag: Order fulfillment with a pocket sorter system - Nils Boysen; Dirk Briskorn; David Füßler; Konrad Stephan (Naval Research Logistics (NRL), 2023)
Due to high real estate costs in urban areas, shop floor space is scarce in most brick-and-mortar stores. Maneuvering newly arrived merchandise through narrow aisles during shelf replenishment is time-consuming for the sales staff and impedes customers. Therefore, many retail chains nowadays aim for store-friendly shipments (SFS). By mirroring the layout of a store in the buildup of its dedicated shipments, the need for a zigzag movement through the store when replenishing shelves can be avoided. On the negative side, however, additional effort arises in the distribution centers. A suitable warehousing system to assemble SFS without excessive effort is a pocket (or pouch or bag) sorter, where each item is put into its separate bag. These bags, filled with items, are automatically transported while hanging from an overhead conveyor and can be sorted into any sequence before being delivered to the workstations that build SFS. This article investigates the assembly of SFS with a pocket sorter and presents scheduling procedures to enhance the efficiency of this process for a given set of store orders. We demonstrate that, despite its notorious complexity, the problem can be solved by simple decision rules with good performance. In a case study, we show that this approach can dramatically reduce the completion times of store orders, resulting in savings of more than 60% of the total working hours compared to a simple real-world policy. Another 30% of reduction can be obtained by standardized store layouts.
Keywords: 650; complexity; pocket sorter; retailing; scheduling; store-friendly shipments